Pengaruh Motivasi, Pengalaman Kerja Dan Kompetensi Dalam Meningkatkan Kinerja Kayawan PT. Dharma Lautan Nusantara - Octy Avriani (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
Performance is the result of one’s work and work behavior in a period of usually 1 year. The outpud produced varies in forms, depends on the organization itself. Manny factors affect performance. In this study, 3 factors were most influenced, namely : Motivation, work experience and competence, Problems regarding performance are also experienced by Pengaruh Motivasi, Pengalaman Kerja Dan Kompetensi Dalam Meningkatkan Kinerja Kayawan PT. Dharma Lautan Nusantara (DLN). The purpose of this research is to first analyze the effect of the independent variables namely Motivation (X1) on the dependent variable in the form of employee performance (Y) on Geyer Pengaruh Motivasi, Pengalaman Kerja Dan Kompetensi Dalam Meningkatkan Kinerja Kayawan PT. Dharma Lautan Nusantara (DLN). Second, to analyze the effect of independent variables, namely work experience (X2) on the dependent variable in the form of employee performance (Y) on Geyer Pengaruh Motivasi, Pengalaman Kerja Dan Kompetensi Dalam Meningkatkan Kinerja Kayawan PT. Dharma Lautan Nusantara (DLN).Third, to analyze the effect of independent variables, namely competence (X3) on the dependent variable in the form of employee performance on Geyer PT. Dharma Lautan Nusantara (DLN. PT. Dharma Lautan Nusantara (DLN. totaling 28 member. Based in the taken as a sampe using a questionnaire to find out their opinions about employee performance. The classic assumption test shows that regression model has fulfilled the normality assumption, there are no multicollinearity The population in the study were all police officer at Geyer Police Station (symptoms and the regsressioin model does not contain heteroscedasticity. The results showed that all the hypotheses submitted were proven true, namely, first, Motivation (X1) had a positive and significant effect on employee performance at Geyer PT. Dharma Lautan Nusantara (DLN), a second, work experience (X2) had a positive and significant effect on employee performance at PT. Dharma Lautan Nusantara (DLN.Third, competence (X3) had a positive and significant effect in employee performance at Geyer PT. Dharma Lautan Nusantara (DLN), and Work Experience (X2) has biggest influenced .This is also shown by the value R2 of 0.808 which means 80,8% of the dependent variable variation, namely employee performance (Y) on by Geyer PT. Dharma Lautan Nusantara (DLN. influenced by independent variables such as Motivation, work experience and competence. While the rest (19.2%) is influenced by other variables outside the model.